EVALUASI PENERAPAN SISTEM BLOK DI PROGRAM KEAHLIAN TEKNIK OTOMOTIF SMK NEGERI 2 YOGYAKARTA : EVALUATION OF THE IMPLEMENTATION OF THE BLOCK SYSTEM IN THE AUTOMOTIVE ENGINEERING EXPERTISE PROGRAM AT SMK NEGERI 2 YOGYAKARTA - Heru Basuki (Department of Automotive Engineering Education, Faculty of Engineering, Yogyakarta State University, 2026)
This study aims to describe the implementation of the block system in the Automotive Engineering Expertise Program of SMK Negeri 2 Yogyakarta, in terms of the suitability of learning implementation, learning quality, and identifying obstacles experienced by students during block system learning. This study is a quantitative descriptive research that uses the CIPP (context, input, process, product) model evaluation approach. Data were obtained through observation, documentation, and questionnaires. The respondents were 12 teachers and 194 students in grades X and XI. The research instruments were validated using content validity and face validity by expert judgment, followed by construct validity test with product moment correlation. Instrument reliability was tested using Cronbach's Alpha. The results showed that block system learning in the Merdeka Curriculum was categorized as appropriate with a score of 75.91%. The quality of block system learning, in terms of teacher qualifications, is categorized as very good with a score of 100%, infrastructure facilities are categorized as very good with a score of 86%, learning implementation is categorized as very good with a score of 82.96%, and student learning outcomes achieve an average score above 75. Students experience obstacles which are categorized as quite obstructed with a score of 42.01%, these obstacles come from internal students 59.82%, systems 28.37%, learning media 8.44%, teachers 2.15%, and learning methods 1.23%.